2023
DOI: 10.1186/s12916-023-02846-2
|View full text |Cite
|
Sign up to set email alerts
|

MECP2 germline mosaicism plays an important part in the inheritance of Rett syndrome: a study of MECP2 germline mosaicism in males

Abstract: Background Germline mosaicisms could be inherited to offspring, which considered as “de novo” in most cases. Paternal germline MECP2 mosaicism has been reported in fathers of girls with Rett syndrome (RTT) previously. For further study, we focused on MECP2 germline mosaicism in males, not only RTT fathers. Methods Thirty-two fathers of RTT girls with MECP2 pathogenic mutations and twenty-five healthy adult males without history and family history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The detection of maternal gonadal mosaicism from oocytes causes technical difficulties, since oocytes can be obtained only by invasive procedure. However, sperm analysis is a possible method of detecting paternal gonadal mosaicism that was studied recently [ 20 , 22 , 23 , 24 , 25 ]. In a Chinese Dravet syndrome cohort, Yang et al reported higher levels of SCN1A mosaicism in sperm samples compared to blood samples of mosaic fathers [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of maternal gonadal mosaicism from oocytes causes technical difficulties, since oocytes can be obtained only by invasive procedure. However, sperm analysis is a possible method of detecting paternal gonadal mosaicism that was studied recently [ 20 , 22 , 23 , 24 , 25 ]. In a Chinese Dravet syndrome cohort, Yang et al reported higher levels of SCN1A mosaicism in sperm samples compared to blood samples of mosaic fathers [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported on the paternal MECP2 gonadal mosaicism of nine fathers’ daughters with Rett syndrome, and in only one of case was mosaicism identified in the blood sample. The research team also found gonadal mosaicism in the sperm samples of healthy males who had no Rett syndrome relatives, and none of these individuals had mosaicism in blood-derived DNA [ 24 ]. A Hungarian case report by Bessenyei et al reported paternal gonadal mosaicism for MED13L -related disorders.…”
Section: Discussionmentioning
confidence: 99%